2014
DOI: 10.1186/1742-9994-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Breeding status and social environment differentially affect the expression of sex steroid receptor and aromatase mRNA in the brain of female Damaraland mole-rats

Abstract: IntroductionThe Damaraland mole-rat (Fukomys damarensis) is a eusocial, subterranean mammal, which exhibits an extreme reproductive skew with a single female (queen) monopolizing reproduction in each colony. Non-reproductive females in the presence of the queen are physiologically suppressed to the extent that they are anovulatory. This blockade is thought to be caused by a disruption in the normal gonadotropin-releasing hormone (GnRH) secretion from the hypothalamus. In order to understand the underlying phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…90 To our knowledge, the interaction of estrogen action and SES on brain development has not been previously studied. However, because social status regulates ESR1 expression in model systems and is associated with altered limbic development, 91,92 an interaction of the same in human development seems credible. The association was strongest when tested across both genders (P-value for rs3020365 × SES = 4.71 × 10 −5 , R 2 overall = 0.17, where gender is a covariate in the model but not significant), when the data was segregated by gender, the association remained significant in males (P-value = 0.03, R 2 = 0.11) but was no longer significant in females.…”
Section: Discussionmentioning
confidence: 99%
“…90 To our knowledge, the interaction of estrogen action and SES on brain development has not been previously studied. However, because social status regulates ESR1 expression in model systems and is associated with altered limbic development, 91,92 an interaction of the same in human development seems credible. The association was strongest when tested across both genders (P-value for rs3020365 × SES = 4.71 × 10 −5 , R 2 overall = 0.17, where gender is a covariate in the model but not significant), when the data was segregated by gender, the association remained significant in males (P-value = 0.03, R 2 = 0.11) but was no longer significant in females.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating estrogens are primarily made in the ovaries and the variation in circulating estrogen level likely accounts for the gender differences in pain and analgesia as well as the variation of pain symptom across the estrous cycle in female subjects . In addition to the peripheral sources of estrogens which may impact on neuronal regulation of pain, many areas in the CNS such as the hypothalamus, the amygdala, and the hippocampus are known to be capable of locally synthesizing estrogens from cholesterol . Therefore, it is possible that locally synthesized estrogens in discrete regions of the pain pathways may impact on pain and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In addition to the peripheral sources of estrogens which may impact on neuronal regulation of pain, many areas in the CNS such as the hypothalamus, the amygdala, and the hippocampus are known to be capable of locally synthesizing estrogens from cholesterol. [16][17][18][19][20][34][35][36] Therefore, it is possible that locally synthesized estrogens in discrete regions of the pain pathways may impact on pain and analgesia. Consistent with this notion, there have been reports demonstrating the expression of aromatase, the key enzyme responsible for the conversion of testosterone to estradiols, in areas important for the ascending transmission of pain signals, such as the dorsal horn of the spinal cord and the nucleus of the solitary tract.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of prolactin receptor in brain sections was detected with antisense RNA probes labeled with 35 S-CTP as described before (Voigt et al 2014). Labeling of the probes with 35 S-CTP (1250 Ci/mmol; Perkin Elmer, Rodgau, Germany) was performed using the Riboprobe System (Promega).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…In Damaraland mole-rats we have previously shown that reproductive status affects the neuroendocrine phenotype of females with reproductively suppressed females having reduced gene expression of steroid hormone receptors in several preoptic-hypothalamic brain regions, including the AVPV and the ARC. Moreover, such females also exhibit reduced Kiss1 expression in the ARC compared to reproductively active females (Voigt et al 2014, Voigt and. In another highly social African mole-rat, the naked mole-rat (Heterocephalus glaber), transcriptome profiling revealed reduced expression of genes involved in dopamine metabolism in reproductively suppressed subordinate females, which remain in a pre-pubertal anovulatory state (Mulugeta et al 2017).…”
mentioning
confidence: 99%